Analisis Ekspresi Cyclin Dependent Kinase (Cdk)6 dan Ki-67 pada Neoplasma Kelenjar Liur - Meyta Riniastuti; Dyah Fauziah; Alphania Rahniayu (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2017)
BackgroundBroad spectrum tumors can arise in salivary glands, giving diagnostic difficulties in some subtypes due to morphological similarities. Immunohistochemistry studies done to differentiate between benign and malignant neoplasms of salivary glands are very few, including Cdk6 and Ki-67. Cdk6’s role in tumorigenesis is halting cellular proliferation and differentiation. Ki-67 is actively expressed in proliferating cells, particularly neoplasms. The objectives are to analyze differences of Cdk6 and Ki-67 expression in benign and malignant salivary gland neoplasms and to analyze the correlation between those two proteins.MethodsThis is an analitic observational study with cross sectional design. Samples were taken proportionally, each 15 samples of benign and malignant salivary gland neoplasms, derived from pathological archives during 1 January 2011-30 June 2013 period. Immunohistochemical staining with Cdk6 and Ki-67 monoclonal antibody were performed. Differences in Cdk6 and Ki-67 expression of both groups were analyzed using Mann Whitney. The correlation between the Ki-67 and Cdk6 expression were analyzed using Spearman.ResultsThere were significant differences in the Cdk6 and Ki-67 expression between benign and malignant salivary gland neoplasms.The expressions of Ki-67 have a cut-off point of 6.50%. There was a significant correlation between Cdk6 and Ki-67 expression in the salivary gland neoplasms.ConclusionExpression of Cdk6 and Ki-67 were low at benign salivary gland neoplasms and high at malignant salivary glands neoplasms. There was significant correlation between Cdk6 expression and Ki-67 expression at benign and malignant salivary gland neoplasms. Although both could differentiate the behavior of neoplasms, Ki-67 was more reliable and applicable.